Financial Performance and Corporate Social Responsibility on Return of Shares - Reniati, Rulyanti Susi Wardhani, Murtiadi Awaluddin, (Jurnal Akuntansi, 2019)
The purpose of this study is to test the hypothesis of the influence of independent variables namely ROI, ROE, EPS, DER, CSR while the dependent variable is Stock Return. This research approach is a fixed effect approach, general effects, and random effects approach. The sample used in this study was 19 Manufacturing Companies listed on the Indonesia Stock Exchange for the 2015-2018 period. The results showed that ROI, ROE, EPS, and DER partially did not affect Stock Return, while CSR partially affected stock returns on Manufacturing Companies listed on the Indonesia Stock Exchange for the 2015-2018 period. This means that the companies sampled in this study stated that CSR is a form of commitment in improving welfare through social and environmental responsibility, CSR also provides long-term benefits by increasing the company's reputation and branding, efficiency, internal party appreciation, and strong profitability.